The Canuck Connection: AERO’s Relationship to Canadian Educators - Glinos, Peter J. (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2023)
AERO, the Alternative Education Resources Organization, is a network of alternativeeducators and institutions that emphasize learner-centred education, particularly thatwhich increases learner autonomy such as free schools. This paper investigates therelationship between AERO and Canadian educators. Based in New York City,AERO’s reach was international. The network raised funds for struggling alternativeschools, advocated against policies designed to standardize education, andsupported reforms to increase school choice. Canadians, particularly Indigenousgroups in Canada, were instrumental in shaping AERO. Educators from Ontario’salternative education sector, as well as the free schools of British Columbia,developed deep connections with AERO over the course of its rise from 1989 to2003. This historical analysis investigates these entanglements by analyzing TheAERO-Gramme Newsletter and The Education Revolution as primary sourcesdocuments.